Analisis Efektivitas Penertiban Penyandang Masalah Kesejahteraan Sosial Di Dinas Sosial Provinsi DKI Jakarta - Jauhar Rosyidi; Dedy Kusna Utama (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The purpose of this study was to analyze the effectiveness of controlling people with social welfare problems (PMKS) by the DKI Jakarta Provincial Social Service. The research method used in this research was descriptive qualitative method, with data collection techniques in the form of questionnaire distribution and literature study. The research questions posed are: what is the analysis of the effectiveness of controlling PMKS by the DKI Jakarta Provincial Social Service; what factors are the obstacles to effectiveness; and what efforts need to be made by the service leaders to overcome these obstacles. The results of the study prove that the effectiveness of controlling people with social welfare problems by the DKI Jakarta Provincial Social Service is good. From the results of interviews, it can be concluded that additional employees are needed. The inhibiting factors for effectiveness are the low number of certified employees and the quantity of human resources that have not met the required number. The suggestion put forward by the researcher is that the DKI Jakarta Provincial Social Service increase the commitment of officers in handling PMKS, improve the supporting facilities and infrastructure for the control, and increases the number of employees or personnel so that the department is able to work wel.